Security Information and Event Management (SIEM) to identify cyberattacks on OWASP standard web - Tia Rahmawati*; Nyoman Bogi Aditya Karna; Sofia Naning Hertina (Universitas Syiah Kuala, 2023)
Cybercriminals usually attack an information security system that contains important and confidential data. Usually frequent attacks are carried out against web applications. Many web application developers do not pay attention to the security side of web applications so that many are exploited by hackers. Security Information and Event Management (SIEM) used will monitor and collect all log reports. SIEM will process the logs to analyze security. All data obtained has been presented in visual form such as graphs. Then the data will be sent to the plugin so that users can more easily access the log report.